‘No Shame at AIME’: Listening to Aboriginal Philosophy and Methodologies to Theorise Shame in Educational Contexts - McKnight, Anthony; Harwood, Valerie; McMahon, Samantha; Priestly, Amy; Trindorfer, Jake (The Australian Journal of Indigenous Education, 2020)
Shame is a ‘slippery’ concept in educational contexts but by listening to Aboriginal philosophy and Country, we can rethink its slipperiness. This article contemplates how multiple understandings of shame are derived from and coexist within colonised educational contexts. We focus on one positive example of Indigenous education to consider how these understandings can be challenged and transformed for the benefit of Indigenous learners. We discuss a mentoring program run by and for Indigenous young people that is successfully impacting school retention and completion rates: The Australian Indigenous Mentoring Experience (AIME). AIME has a rule, ‘No Shame at AIME’, with the view to minimising shame as a barrier to engaging with Western education. But is this as beneficial as might first appear? Might this erode important cultural understandings of shame necessary in Indigenous education? Instead, could shame be repositioned to better align with original cultural meanings and purposes? We philosophise about the AIME rule with Yuin Country and stories from Country along with our observational and interview data. We argue AIME does not so much ‘remove’ shame as reposition it to better align with Aboriginal cultural educational practice, which positively impacts mentees.